Singularity‐free non‐linear controller for a model‐scaled autonomous helicopter. Issue 2 (1st January 2016) - Zou, Yao; Huo, Wei
Abstract : A singularity‐free non‐linear controller is proposed for trajectory tracking of a model‐scaled autonomous helicopter. The helicopter model is firstly decomposed into a nominal one with unmodelled dynamics. Based on the decomposed model, the controller is designed with the hierarchical inner–outer loop strategy. The outer position loop controller is designed with hyperbolic tangent functions, and criteria for controller parameter selections are developed to realise the position tracking and to obviate singularity in deriving the command attitude from the position loop controller. The inner attitude loop controller is designed based on barrier Lyapunov function and backstepping technique to achieve the attitude tracking without singularity during the tracking process. In addition, in order to improve the tracking performance, observers are employed to compensate the unmodelled dynamics. Simulation of two manoeuvres verify the proposed theoretical results.